2009
DOI: 10.4049/jimmunol.0804377
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Affinity-Enhancing Mutations in a Myelin Oligodendrocyte Glycoprotein-Specific TCR Alter Specificity and Generate New Self-Reactivity

Abstract: We describe a simple iterative approach to augment TCR affinity, which we studied using a myelin oligodendrocyte glycoproteinspecific TCR. We hypothesized that single amino acid modifications in TCR CDR3 could enhance TCR sensitivity through focal interactions with antigenic peptide while minimizing the risk of cross-reactivity observed previously in TCR more broadly mutagenized using in vitro evolution techniques. We show that this iterative method can indeed generate TCR with Ag sensitivity 100-fold greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…We comprehensively investigated the autoreactive strength of this unprecedentedly large set of human iNKT TCRs and identified three CDR3β amino acid sequence motifs that were associated with strong autoreactivity: a VD region with 2 or more acidic amino acids, usage of the Jβ2-5 allele, and a CDR3β region of 13 amino acids in length. Our findings are underpinned by the previous reports that an acidic amino acid composition, J usage, and the CDR3β region amino acid length individually affected the affinities of conventional TCRs [35-37]. Importantly, human iNKT TCRs highly reactive for self-ligands reported to date indeed harbor 2 out of the 3 sequence motifs (Supplementary Table 1) [2, 10, 34, 38].…”
Section: Discussionsupporting
confidence: 64%
“…We comprehensively investigated the autoreactive strength of this unprecedentedly large set of human iNKT TCRs and identified three CDR3β amino acid sequence motifs that were associated with strong autoreactivity: a VD region with 2 or more acidic amino acids, usage of the Jβ2-5 allele, and a CDR3β region of 13 amino acids in length. Our findings are underpinned by the previous reports that an acidic amino acid composition, J usage, and the CDR3β region amino acid length individually affected the affinities of conventional TCRs [35-37]. Importantly, human iNKT TCRs highly reactive for self-ligands reported to date indeed harbor 2 out of the 3 sequence motifs (Supplementary Table 1) [2, 10, 34, 38].…”
Section: Discussionsupporting
confidence: 64%
“…An overall enhanced compatibility with MHC may thereby lead to the increased utilization of public TCR in diverse responses. An element of enhanced self-reactivity would be expected to accompany any generically increased binding fitness of TCR for MHC, and indeed this has been observed in mutational analyses increasing TCR affinity (39, 40). …”
Section: Discussionmentioning
confidence: 91%
“…4). For MOG 35-55 , evidence suggested that amino acid residues P-1 and P-2 outside of the core nonamer contribute to MHC anchoring and to TCR binding in individual clones (44, 45, 54, 55) with implications for T cell recognition of NFM 15-35 (28). We focused on modulating NFM at P1 (T20Y) to mirror MOG at that position because Petersen et al .…”
Section: Discussionmentioning
confidence: 99%